2020
DOI: 10.3390/ijms21186483
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Cardiovascular Disease, with Emphasis on Hypertension, Atherosclerosis, and Heart Failure

Abstract: Vitamin D deficiency is the most common nutritional deficiency, affecting almost one billion people worldwide. Vitamin D is mostly known for its role in intestinal calcium absorption and bone mineralization. However, the observation of seasonal changes in blood pressure and the subsequent identification of vitamin D receptor (VDR) and 1α-hydroxylase in cardiomyocytes, as well as endothelial and vascular smooth muscle cells, implicated a role of vitamin D in the cardiovascular system. Animal studies provided co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
129
0
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(153 citation statements)
references
References 111 publications
(137 reference statements)
4
129
0
20
Order By: Relevance
“…Binding of 1,25(OH) 2 D induces a conformational change in the vitamin D receptor (VDR), leading to hetero-dimerization with the retinoid X receptor and ultimately to translocation of this complex into the nucleus, where it binds to vitamin D response elements in the promoter region of target genes. A variety of extra-renal cells also exhibit 1α-hydroxylase activity, indicating that in these cells the biological effects are determined by the sum of circulating and locally produced 1,25(OH) 2 D [ 14 ].…”
Section: Vitamin D Metabolismmentioning
confidence: 99%
“…Binding of 1,25(OH) 2 D induces a conformational change in the vitamin D receptor (VDR), leading to hetero-dimerization with the retinoid X receptor and ultimately to translocation of this complex into the nucleus, where it binds to vitamin D response elements in the promoter region of target genes. A variety of extra-renal cells also exhibit 1α-hydroxylase activity, indicating that in these cells the biological effects are determined by the sum of circulating and locally produced 1,25(OH) 2 D [ 14 ].…”
Section: Vitamin D Metabolismmentioning
confidence: 99%
“…Considering that numerous clinical studies have reported that vitamin D supplementation mitigates cardiovascular disease [158,159], it is worth mentioning that over the years various groups have observed a link between vitamin D and irisin expression. In diabetic animal models, vitamin D increases irisin expression [160].…”
Section: Irisin: Nutritional Interventionsmentioning
confidence: 99%
“…Vitamin D has been implicated in the regulation of several pathways, besides its well-known role as regulator of the calcium-phosphate metabolism, it has been suggested that it may be implicated in immune system modulation [ 29 ], in the regulation of muscle strength and metabolism and in the cognitive decline [ 51 ]. Moreover, hypovitaminosis D has been considered risk factors for CVD [ 52 ]. Both cross-sectional [ 53 54 55 ] and longitudinal studies [ 56 ] suggested a role for hypovitaminosis D in predicting the development of cardio metabolic risk factors as MetS and diabetes.…”
Section: Vitamin D Deficiency and Metabolic Syndromementioning
confidence: 99%